The three-cornered sun a linguistic analysis - San Juan, Reylin K.; Prof. Epistola, Nieves B. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1996)
This paper investigates the effectiveness of Halliday's systematic-functional grammar, especially the transitivity system, in analyzing the underlying movement of the novel The Three-Cornered Sun by Linda Ty-Casper. It aims to answer the questions how the functional analysis of the text helps in the verification of its interpretation. The excerpts analyzed were taken from each of the four books of the novel. The passages are randomly chosen to prove that the linguistic pattern recognized appears throughout the whole text. Hence, this is a study of how interpretations are effectively achieved through a closer look at the significance of patterns, ordinary or otherwise, in the meaning of the text. The excerpts are analyzed with the application of Halliday's transitivity system. The transitivity function recognized three types of processes: material (action), mental, and relational processes. Each of these processes have their corresponding participants: actor or instrument for the material process, senser for the mental processes and carrier for the relational. The circumstantial features and the modifying clauses (some) are not given much attention for they do not directly affect the study. This paper was able to show how the systemic-functional analysis is able to answer why or how a text is interpreted in such and such a way and what factors contribute to such interpretation.
Thesis--University of the Philippines Diliman
Includes bibliographical references (pages 42-43).